Application of Cerium (IV) as an Oxidimetric Agent for the Determination of Ethionamide in Pharmaceutical Formulations. (13th October 2016) - Basavaiah, Kanakapura; Qarah, Nagib A. S.; Abdulrahman, Sameer A. M.
Abstract : Two simple methods are described for the determination of ethionamide (ETM) in bulk drug and tablets using cerium (IV) sulphate as the oxidimetric agent. In both methods, the sample solution is treated with a measured excess of cerium (IV) solution in H2 SO4 medium, and after a fixed standing time, the residual oxidant is determined either by back titration with standard iron (II) solution to a ferroin end point in titrimetry or by reacting with o-dianisidine followed by measurement of the absorbance of the orange-red coloured product at 470 nm in spectrophotometry. In titrimetry, the reaction proceeded with a stoichiometry of 1 : 2 (ETM : Ce (IV)) and the amount of cerium (IV) consumed by ETM was related to the latter's amount, and the method was applicable over 1.0–8.0 mg of drug. In spectrophotometry, Beer's law was obeyed over the concentration range of 0.5–5.0  μ g/mL ETM with a molar absorptivity value of 2.66 × 10 4  L/(mol·cm). The limits of detection (LOD) and quantification (LOQ) calculated according to ICH guidelines were 0.013 and 0.043  μ g/mL, respectively. The proposed titrimetric and spectrophotometric methods were found to yield reliable results when applied to bulk drug and tablets analysis, and hence they can be applied in quality control laboratories.